2012
DOI: 10.1093/scan/nss141
|View full text |Cite
|
Sign up to set email alerts
|

Sustained neural activity to gaze and emotion perception in dynamic social scenes

Abstract: To understand social interactions, we must decode dynamic social cues from seen faces. Here, we used magnetoencephalography (MEG) to study the neural responses underlying the perception of emotional expressions and gaze direction changes as depicted in an interaction between two agents. Subjects viewed displays of paired faces that first established a social scenario of gazing at each other (mutual attention) or gazing laterally together (deviated group attention) and then dynamically displayed either an angry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 49 publications
3
18
1
Order By: Relevance
“…It is likely that the processing of gaze direction, head orientation, and gaze motion recruit different close-by areas in posterior occipito-temporo-parietal regions, which may differentially impact and sum up at the level of the scalp N170, depending on the stimulus and task at hand. Our result is in line with previous studies that used static faces under frontal view and found enhanced N170 for faces displaying averted as compared to direct gaze ([18, 19], see also [111]).…”
Section: Discussionsupporting
confidence: 93%
“…It is likely that the processing of gaze direction, head orientation, and gaze motion recruit different close-by areas in posterior occipito-temporo-parietal regions, which may differentially impact and sum up at the level of the scalp N170, depending on the stimulus and task at hand. Our result is in line with previous studies that used static faces under frontal view and found enhanced N170 for faces displaying averted as compared to direct gaze ([18, 19], see also [111]).…”
Section: Discussionsupporting
confidence: 93%
“…Video clips have comprised realistic depictions of social interactions, digital animations of human‐like avatars, and point‐light displays and stick‐figure displays of human movements . Finally, whereas many stimuli portrayed target individuals from head/neck to toe, others showed only people's upper bodies, facial expressions, or hand movements …”
Section: People Watching: Toward a Neuroscientific Perspectivementioning
confidence: 99%
“…A prominent negativity at around 170–220 ms (N170) post-motion onset is seen in the posterior scalp to apparent motion of a natural face (Puce et al, 2000) or a line-drawn face (Puce et al, 2003). A corresponding magnetoencephalographic response, the M170, has also been described to the apparent motion of natural faces (Watanabe et al, 2001) or to facial avatars (Ulloa et al, 2012) Larger and earlier N170s occurred to gaze aversions relative to direct gaze movements in both natural faces and isolated eyes, and to mouth opening relative to mouth closure (Puce et al, 2000). Similar results have been demonstrated using images of line-drawn faces making mouth movements (Puce et al, 2003).…”
Section: Introductionmentioning
confidence: 99%